Non-State Actors in Peace Education and Conflict Management amid Ethnic Militias and Resource Competition in Africa: Implication for Regional Security - Nura Umar Manya Manya; Usman Yusuf; Mustapha Barau (An-Nasyi'in: Jurnal Ilmu Pendidikan, 2026)
This study examines the role of non-state actors in managing ethnic militias and competition over natural resources in Africa and their implications for regional security. The findings indicate that ethnic militias and resource-based competition contribute significantly to conflict escalation, state fragility, cross-border insecurity, and humanitarian crises. Non-state actors play important roles in conflict mediation, humanitarian assistance, security provision, and governance support, particularly in areas where state capacity is limited. However, their effectiveness is often constrained by weak regulatory frameworks, fragmented authority, legitimacy concerns, and insufficient coordination with state institutions. The study concludes that while non-state actors are essential in addressing Africa’s security challenges, stronger institutional coordination and regulation are necessary to achieve sustainable peace and regional stability.